Colesevelam improved lipoprotein particle subclasses in patients with prediabetes and primary hyperlipidaemia (2013)
Background: A randomised, double-blind, placebo-controlled study evaluated lipid- and glucose-lowering effects of colesevelam in patients with prediabetes and primary hyperlipidaemia. We report the effect of colesevelam on lipoprotein particle concentration and particle size (determined by nuclear magnetic resonance spectroscopy) in these patients. Methods: Adults with prediabetes (World Health Organization criteria), low-density lipoprotein cholesterol(LDL-C) ? 100 mg/dL (?2.6 mmol/L) and triglycerides less than 500 mg/dL ( less than 5.6 mmol/L) were randomised to colesevelam 3.75 g/day or placebo for 16 weeks. The intent-to-treat population comprised 103 colesevelam and 106 placebo recipients. Results: At the end of the study, mean reduction from baseline in total LDL particle concentration was significantly greater with colesevelam versus placebo (mean treatment difference: ?113 nmol/L; p = 0.02). Increases in total very low-density lipoprotein particle concentration (VLDL-P) and high-density lipoprotein particle concentration (HDL-P) did not differ significantly between the groups; however, with colesevelam versus placebo, there were significantly (p less than 0.05) greater increases in large and medium VLDL-P and large HDL-P and reductions in small VLDL-P. Mean size increases were significantly greater with colesevelam for VLDL (mean treatment difference: 5.3 nm; p less than 0.0001) and HDL (0.1 nm; p = 0.002). Conclusions: Colesevelam improved the overall atherogenic lipoprotein profile in adults with prediabetes and primary hyperlipidaemia, despite potentially less favourable changes in VLDL particles. © The Author(s) 2012.